THE EFFECT OF EMPLOYEE ENGAGEMENT AND WORK-LIFE BALANCE ON EMPLOYEE PERFORMANCE AT BAZNAS TANGERANG CITY - Darojat, Ilma; Istiqomah, Istiqomah (Univesitas Muhammadiyah Tangerang, 2024)
TThe purpose of this study is to determine the influence of employee engagement and work-life balance on employee performance at BAZNAS Tangerang City. This study uses a quantitative approach. The population in this study is 38 employees at BAZNAS Tangerang City with a sample of 38 respondents. The sampling technique used is saturated samples. Primary data collection was obtained from the distribution of questionnaires. The analysis technique used is multiple linear regression analysis using SPSS version 26 software. The results of the study showed that partially the employee engagement variable (X1) had a positive and significant effect on employee performance (Y), this was shown by the ttable > tcount of 3.339 > 2.0280 and a significance value of 0.002. For the variable work life balance (X2) has a positive and significant effect on employee performance (Y), this is shown by the tcount > ttable, namely 2.472 > 2.0280 and a significance value of 0.018. And simultaneously the variables employee engagement (X1) and work life balance (X2) have a positive and significant effect on employee performance (Y), namely Fcal > Ftabel of 15.799 > 3.27 and a significance value of 0.000. With a determination coefficient of 47.4% and the remaining 52.6% is influenced by other factors that were not studied in this study.